Tata Kelola Keuangan BUMDesma untuk Mewujudkan Tujuan Pembangunan Berkelanjutan Desa di Kecamatan Kalibagor, Kabupaten Banyumas - Arofah, Triani; Ramadhanti, Wita; Rusmana, Oman (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2023)
One of the government's two national programs, the Post-pandemic National Economic Recovery, and the other, the Acceleration of the Village-Sustainable Development Goals (SDGs), relies heavily on village owned enterprises, or BUMDes. Thus, in order for BUMDes Joint to become the engine that propels the village economy, it is necessary to have good and accurate financial management. The purpose of this research is to examine and characterize BUMDes Bersama's financial management in light of the concepts of open, accountable, participatory, and disciplined village finance management. Data for this qualitative study came from a variety of sources, including documentation and non-structured interviews. Although the Joint BUMDes has put the financial management principles into practice, some of these principles, particularly those pertaining to accountability, transparency, and budget order and discipline, are still lacking. The Joint BUMDes business unit's inability to produce comprehensive financial reports due to a lack of manpower and an inadequate system for making publicly available financial data is the driving force behind the subpar execution of this principle.